Is it better to seek or to receive? A dual-factor model of social support - Hamby, Sherry; Taylor, Elizabeth; Mitchell, Kimberly; Jones, Lisa; Newlin, Chris (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2020)
Objectives: This study adopts a dual-factor approach to examine the association of seeking and receiving social support with 6 indicators of current functioning and 14 psychosocial strengths.Methods: A survey completed by 440 youth ages 10 to 21 (M = 16.38, SD = 3.04) assessed strengths, functioning, and victimization. Youth were classified into four groups: Interconnected (high on social support seeking and receiving; 33% of sample), Rebuffed (high on social support seeking, low on social support receiving; 12%), Tended (low on social support seeking, high on social support receiving; 16%), and Isolated (low on social support seeking and receiving; 39%).Results: Controlling for age, gender, and victimization, the social support group was associated with each meaning making, regulatory, and interpersonal strength, and every indicator of current functioning except trauma symptoms. The Isolated group scored lowest on all measures and the Interconnected group scored highest on 19 of 20 measures. The mixed profile groups fell between these extremes. Notably, the Rebuffed group reported higher levels of some strengths and non-theistic spiritual well-being than the Tended group. The Tended group was never significantly higher than the Rebuffed group.Implications: Individual skills and attitudes regarding helpseeking may be more impactful than social support provided by others. Rebuffed youth may be steeling themselves in other strengths when the social environment is not supportive.